Analytic Continuation of Diagonals of Laurent Series for Rational Functions - Pochekutov, Dmitry Yu (Journal of Siberian Federal University. Mathematics & Physics, 2021)
We describe branch points of complete q-diagonals of Laurent series for rational functions in several complex variables in terms of the logarithmic Gauss mapping. The sufficient condition of non-algebraicity of such a diagonal is proven